HUBUNGAN ASUPAN ZAT GIZI MIKRO DENGAN KADAR HEMOGLOBIN REMAJA PUTRA USIA 11-19 TAHUN DI PANTI ASUHAN DARUT TAQWA KOTA SEMARANG TAHUN 2016 - Debby Rizky Amelia; M. Zen Rahfiludin; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2016)
Adolescence is the age where the growth spurt. Physical activity of adolescent boys is greatly increased, causes an increase in body mass, blood volume and red blood cell count. So, if the consumption of various sources of nutrients are not improved, there may be deficiencies of micronutrients such as iron, zinc, copper, folic acid and vitamin B12 that related to hemoglobin levels. Anemia is a condition in which the hemoglobin and the red blood cell count is less than normal, as the result from the deficiency of one or more essential nutrient. The purpose of the study is to analyze the relationship between micronutrients intake and hemoglobin levels in adolescent boys of ages 11-19 in Panti Asuhan Darut Taqwa Semarang. This study includes observational analytical research with the cross-sectional approach. The sampling technique used in this study is total sampling of 43 people. The data were collected through form filling of semi-quantitative FFQ and measurement of hemoglobin levels with cianmethemoglobin method. The data analysis are included univariate and bivariate analysis. The results shows that the average intake of iron consumed by the respondent is 14.34 mg/day (88.1%), the average intake of zinc is 8.65 mg/day (51.4%), the average intake of copper is 1.64 mg/day (203.2%), the average intake of folic acid is 286.11 µg/day (71.5%) and the average intake of vitamin B12 is 3.35 µg/day (149.2%). While the average of hemoglobin levels is 11.1 g/dL. The result of the bivariate analysis shows that there is a relationship between iron intake (p=0.001), zinc intake (p=0.001), copper intake (p=0.001), and folic acid intake (p=0.001) and hemoglobin levels. There is no relationship between vitamin B12 and hemoglobin levels (p = 0.242). The stakeholders is suggested to improve the delivery of highly nutritious food to the students.